Hybrid approach with composite mesh repair of a massive right-sided congenital Bochdalek’s hernia in an adult: A case report - Prem M. Shah; Akshat K. Vadaliya; Haryax V. Pathak (International Journal of Abdominal Wall and Hernia Surgery)
Congenital diaphragmatic hernia (CDH) is a rare developmental anomaly typically observed in neonates but can occasionally present in adults. CDH results from incomplete diaphragm development, leading to herniation of abdominal organs into the thoracic cavity, causing respiratory and gastrointestinal issues. This report discusses a 23-year-old male diagnosed with a right-sided congenital Bochdalek’s hernia. The patient presented with generalized abdominal pain, nausea, and respiratory symptoms. Imaging revealed a significant right diaphragmatic defect with herniation of multiple abdominal organs into the thoracic cavity. Initial laparoscopic attempts to reduce the hernia were unsuccessful due to dense adhesions, necessitating an open surgical approach. The herniated organs were reduced, and the diaphragmatic defect was repaired using non-absorbable sutures and a composite mesh. Postoperative recovery was complicated by transient abdominal compartment syndrome, which was managed conservatively. The patient recovered well and remained symptom-free during the 6-month follow-up period.